Infrastructure Development and Population Dynamics as Determinants of Regional Economic Growth: Evidence from Java Island, Indonesia - Septriani Septriani; Muhammad Azizurrohman (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2023)
This study investigates the impact of infrastructure development and population growth onregional economic performance across the provinces of Java Island, Indonesia. Using panel datacovering the period from 2016 to 2021 obtained from the Ministry of Finance and the CentralBureau of Statistics, the study applies a Random Effect Model to assess the contribution of roadinfrastructure, electricity infrastructure, and population to provincial Gross Regional DomesticProduct (GRDP). The empirical results reveal that road and electricity infrastructure exertpositive and statistically significant effects on GRDP, indicating that improvements intransportation networks and energy supply directly enhance regional productivity and economicactivity. In contrast, population growth shows no significant effect, suggesting that demographicexpansion alone does not guarantee economic advancement without correspondingemployment opportunities and infrastructure quality. The model explains 84.14 percent of thevariation in GRDP, confirming the strong explanatory power of infrastructure variables. Thesefindings highlight the importance of sustained investment in physical infrastructure to promoteinclusive and balanced economic growth across regions